Pipeline load testing - Izabela Kinga Nieradko 1993- (2021)
Tool to allow load testing of metric pipeline for a company Netapp. This tool allows us to send big data responses in order to see how does the pipeline behaves under different load pressure. Netapp Iceland ehf. Gunnarr Baldursson gunnarr.baldursson@netapp.com